Intro to Coding Using Python at the Worcester Public Library. - Friedenthal, Melody (Information Technology & Libraries, 2020)
The Worcester Public Library (WPL) offers several Digital Learning courses to our adult patrons, and among them is "Intro to Coding Using Python". This 6-session class teaches basic programming concepts and the vocabulary of software development. It prepares students to take more intensive, college-level classes. The Bureau of Labor Statistics predicts a bright future for software developers, web developers, and software engineers. WPL is committed to helping patrons increase their "hireability" and we believe our Python class will help patrons break into these lucrative and gratifying professions... or just have fun.